Schedulung European soccer leagues: Models, methods, and applications - Thomas Bartsch; Andreas Drexl; Stefan Kröger (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 2002)
Generating a regular season schedule is a demanding task for any sports league. In Europe, the creation of a suitable schedule for every national top soccer league not only has to address numerous conflicting inner-league requirements and preferences. Additionally, the games of the European Cup matches (Champions League, UEFA Cup, National Cup Winners) have to be taken into account. In this paper we consider the case of Germany and Austria, that is the planning problem the "Deutsche Fußball-Bund" (DFB) and the "Österreichische Fußball-Bund" (ÖFB) are confronted with. For both leagues we develop models and algorithms which yield reasonable schedules quickly. The models borrow their expressive power from so-called partially renewable resources. Our approach generates schedules which have been accepted for play once by the DFB and five times by the ÖFB.
Keywords: 650; Scheduling/timetabling; combinatorial optimization; sport; Fußball; Terminplanung; Scheduling-Verfahren; Theorie; Deutschland; Österreich